Individual-level social capital is associated with depressive symptoms among middle-aged community dwellers in rural Vietnam: a cross-sectional study. Issue 12 (6th December 2022) - Do, An Dang; Pham, Thuy Thi Phuong; Nguyen, Chau Que; Hoang, Dong Van; Fukunaga, Ami; Stickley, Andrew; Yazawa, Aki; Phan, Danh Cong; Hachiya, Masahiko; Jimba, Masamine; Huynh, Dong Van; Le, Huy Xuan; et al.
Abstract : Objectives: There has been comparatively little research on the association between social capital and depressive symptoms in low- and middle-income countries. To address this deficit this study examined the association among middle-aged adults in rural Vietnam. Design: A cross-sectional study. Setting: Data came from the baseline survey of the Khánh Hòa Cardiovascular Study, which is an ongoing prospective cohort study aiming to elucidate the determinants of cardiovascular diseases. Participants: A total of 3000 people aged 40–60 years old residing in rural communes in Khánh Hòa province, Vietnam. Exposure of interest: Cognitive social capital (ie, low, middle and high) and structural social capital (in terms of social participation; yes or no) were assessed via a questionnaire. Primary outcome measure: Depressive symptoms were assessed with the 11-item Center for Epidemiologic Studies Depression Scale. Results: A robust Poisson regression model revealed that adults in the highest versus lowest cognitive social capital tertile had a 61% lower prevalence of depressive symptoms (prevalence ratio (PR)=0.39, 95% CI=0.31 to 0.49). Individuals with higher structural social capital were also significantly less likely to experience depressive symptoms (PR=0.74, 95% CI=0.61 to 0.90). Conclusion: In a cohort of 3000 middle-aged rural residents in Vietnam, both cognitive and structural social capital assessed at the individual level were inversely associated with the prevalence of depressive symptoms.